Penerapan Pembelajaran Jigsaw dalam Peningkatan Kemampuan Berpikir Kombinatorik Mahasiswa Teknik Industri - Rahmi, Hanifatul; Zamista, Adelia Alfama (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2020)
This study was based on the advantages that faced by the Industrial Engineering Study Programme Students when follow lecture in Mathematical field. This study was a quasi research with using the one group retest-postest design. This study aims to analyze the gain of students’ combinatoric thinking ability through cooperative learning model type Jigsaw in Differential Application topic at Calculus course. The research sample are 30 students of Industrial Engineering Study Programme. The independent variable in this study was combinatoric thinking ability, while the dependent variable was cooperative learning model type Jigsaw. This study used the combinatoric thinking ability test instrument that has testet about its validity, reability, the difficulty level and the differentiator power. The research result showed that there was a gain of student’s combinatoric thinking ability through cooperative learning model type Jigsaw with n-gain value is 0.56 point and on medium level. The number of students who has combinatoric thinking ability was increased from 6 people to 14 people. The lecturer and the student’s activities have followed the rule of cooperative learning model type Jigsaw as well therefore it can improve student’s combinatoric thinking ability.